Los «parerga» del manuscrito autógrafo: el ejemplo de «Basta callar» de Calderón (BNE, Res. 19) - Folger, Robert (Anuario Calderoniano, 2015)
Las tachaduras y atajos del manuscrito, en parte autógrafo, Res. 19 de la Biblioteca Nacional de España de la comedia Basta callar de Pedro Calderón de la Barca pueden interpretarse como parerga, o sea, elementos del marco suplementario del texto que es la condición de la significación de la obra. Las partes suprimidas indican que el suplemento del tema principal de la obra, la necesidad por parte de los poderosos de sacrificar sus pasiones, es la perversión, tal como se entendía en la época: «la corrupción de las costumbres». «The Parerga of An Autograph Manuscript: The Example of Basta callar of Calderón (BNE, Res. 19)» Manuscript Res. 19 of the Biblioteca Nacional de España, a copy of Calderón’s court spectacle Basta callar, partially written by the author himself, paradigmatically illustrates the logic and working of Jacques Derrida’s notion of the parergon («frame»). In the manuscript, we observe the (graphic) intrusion of the frames into the text. These frames were used by stage directors and/or the authors to mark sections to be suppressed in a particular representation. They both contain and suppress elements which are dispensable because they seem not to contribute to our understanding of the central notions of the play: The high nobility’s renunciation of passion for the sake of state and power. A detailed analysis of the barred materials shows that perversion, in its 17th-century meaning of a corruption of the «good customs» (ethical, sexual, and religious), is the necessary supplement of the logic of power. PALABRAS CLAVE / KEYWORDS: Calderón, Derrida, Basta callar, manuscrito, parergon / Calderón, Derrida, Basta callar, manuscript, parergon.